Cancer burden and trends in China: A review and comparison with Japan and South Korea - Sun, Dianqin (Chin J Cancer Res, 2020)
OBJECTIVE: To summarize the cancer burden and trends in China, compare the differences among China, Japan, and South Korea and discuss possible causes of the disparities. METHODS: Incidence and mortality data were extracted from the online cancer database including the GLOBOCAN 2018 and the Global Burden of Disease Study 2017. Trend analysis was conducted using the join-point analysis, and annual percent changes were calculated. RESULTS: Cancers resulted in approximately 62.9 million disability-adjusted life years (DALYs) in China in 2017. Lung cancer had the greatest contribution, followed by liver cancer, stomach cancer, and esophageal cancer. The trajectory of progress in the reduction of liver and stomach cancers was observed in China. However, China still faced a heavy burden of lung cancer and a growing burden of cancers related to westernized lifestyle such as colorectal cancer, while Japan and South Korea have achieved reductions in colorectal cancer and lung cancer, respectively. Besides, China had a lower age-standardized cancer incidence rate but higher cancer mortality and DALY rates than Japan and South Korea. CONCLUSIONS: China is in the cancer transition stage with a rising burden of colorectal, prostate, and breast cancers along with a heavy burden of lung and upper digestive tract cancers. Taking into consideration the effectiveness of screening and tobacco control in Japan and South Korea, improvement in the current tobacco control policy and cancer screening systems may contribute to cancer control in China.